Plugging the Gap and Niching the NICHE: Nursing Informatics Competencies for Higher Education - Cavite, France Allan M.; Acob, Joel Rey U.; Selasa, Pius (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
Despite the rapid advancement and evolution of nursing informatics applications in healthcare, the incorporation and refurbishing of undergraduate informatics competencies in the curriculum has been organized. the integration of informatics in the Philippine curriculum began decade ago. However, it is still not identified whether these initiatives are successful in enhancing NI skills among graduates considering the low rate of technology utilization by most hospitals in the country. As a result, it requires a global need for nursing informatics competencies to be updated and revisited into the nursing curriculum. The objective of this study is to gather accord from the literature and to determine the definition of fundamental nursing informatics competencies for baccalaureate nursing programs in the Philippines. A review of related studies and corroboration of related literature such as different nursing curricula, perspectives of nursing informatics competencies in every country and to the resource organizations standards providing trainings, conducts research and guide HEIs was performed. International and local organizations were preparing the advancement of informatics through research, trainings, continuous quality improvement, and innovations in HIT. The identified common ground plugging the gap in nursing informatics competencies were nursing care and management proficiencies, information literacy and management, computer skills, health facilities’ technology resources, and ethics and legal understanding in HIT (NICHE). The prior competencies (basic computer skills, information literacy, and information) should be adaptable to local differences and consulted to industry partners and stakeholders. These attempts at competency standardization have to be balanced with suppleness to account for local variations and conditions.